4H-SiC MOSFETs with a stable protective coating for harsh environment applications - Daves, Walter; Krauss, A.; Haeublein, Volker; Bauer, Anton; Frey, Lothar (2012)
Keywords: 4H-SiC; Harsh environment; High temperature; MOSFET; Protective coating; Reliability

Comparative study on metallization and passivation materials for high temperature sensor applications - Daves, Walter; Krauss, A.; Le-Huu, M.; Kronmüller, S.; Haeublein, Volker; Bauer, Anton; Frey, Lothar (2011)
Keywords: High-temperature; Metallization; Passivation; PECVD; Platinum; Platinum-rhodium

Electrical characterization of lateral 4H-SiC MOSFETs in the temperature range of 25 to 600 °C for harsh environment applications - Daves, Walter; Krauss, A.; Häublein, Volker; Bauer, Anton; Frey, Lothar (2011 IMAPS International Conference on High Temperature Electronics Network, HiTEN 2011, 2011)
Keywords: Harsh environment; 4H-SiC; MOSFET; High-temperature; Transducer

Structural and reliability analysis of ohmic contacts to SiC with a stable protective coating for harsh environment applications - Daves, Walter; Krauß, Andreas; Häublein, Volker; Bauer, Anton; Frey, Lothar (ECS Journal of Solid State Science and Technology, 2012)
Ohmic contacts to SiC are the most crucial device components for the reliability of SiC devices in harsh environments. This work aimed at improving the reliability of Ni and Ti ohmic contacts to SiC using stable protective coatings. The stability of the contacts was investigated by means of long-term aging at 600°C in air and air/moisture ambient as well as temperature cycling up to 700°C in air/moisture ambient. The structural and chemical properties were investigated by means of XPS depth profiling and TEM analysis. The beneficial effect of a stable protective coating inhibiting the migration of oxygen/moisture into the contact metallization is demonstrated. Excellent reliability benchmarks are shown for Ti ohmic contacts with a PECVD a-SiOx/a-SiC protective coating. The results are very promising for harsh environment applications. © 2012 The Electrochemical Society.